A new concept of development. basic tenets - Perroux, François, 1903-1987 (Routledge library editions. Development., 2014)
First published in 1983, François Perroux's A New Concept of Development analyses the major paradox of our era: the desire for progress and the mistrust of its consequences. The authors argues that the approach to the question of development may be the key to understanding both the present and what the future brings, representing a pattern which will seek to shape man's potential to his designs. By analysing the ideas and theories propounded by the economic approach the author's aim is to clarify both the meaning and direction of research in development. A scientific, oriented economy and effic.